Hidden in the urban parks of New York City: Themira lohmanus, a new species of Sepsidae described based on morphology, DNA sequences, mating behavior, and reproductive isolation (Sepsidae, Diptera) - Ang, Yuchen (PENSOFT PUBLISHERS, 2022)
10.3897/zookeys.698.13411